A retrospective analysis of migraine prophylaxis with anti-CGRP monoclonal antibodies at the hospital of Lithuanian University of Health Sciences Kaunas Clinics - Karpavičiūtė, V.; Statkevičienė, K.; Žemgulytė, G. (Neurologijos seminarai, 2023)
Background. Migraine is a primary headache disorder described by episodic attacks that can progress to chronic migraine. Preventive treatment of anti-calcitonin gene-related peptide monoclonal antibodies (anti-CGRP mAbs) is currently being widely investigated worldwide.Materials and methods. A total of 85 patients with migraine were enrolled in a retrospective study conducted in 2019-2021. Demographic and clinical data were collected and analyzed. Subjects were divided into groups by migraine course: chronic migraine (CM) and episodic migraine (EM), and according to the medicine used (erenumab, fremanezumab). Treatment efficacy was assessed at 3 and 6 months after the start of treatment. A reduction of >50% in monthly headache days (MHDs) was considered a good response. Statistical analysis was performed using IBM SPSS statistics 27.0, the χ² test of homogeneity, Fisher’s exact, Student’s t, and Mann-Whitney tests.Results. Of the 85 migraine patients, 75 (88.2%) were women. EM was diagnosed in 33 (38.8%) and CM in 52 (61.2%) patients. After treatment, the number of MHDs was significantly reduced in both anti-CGRP mAbs therapy groups (p
Keywords: chronic; episodic migraine; erenumab; fremanezumab; treatment